PLATELET DEMAM BERDARAH DENGUE - PR Ayu; U Bahrun; M Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Dengue Hemorrhagic Fever (DHF) is usually diagnosed based on the clinical symptoms and laboratory examinations of platelet index, including platelets count,: the Mean Platelet Volume (MPV), and the Platelet Distribution Width (PDW), but the most common use is the serological tests which can distinguish between the primary and secondary infection. The aim of this study was to know the three parameters in primary and secondary infections of the dengue patients during the hospitalization. This study was performed by a retrospective cohort study at the pediatric ward of Dr. Wahidin Sudirohusodo Hospital Makassar during the period of March−June 2010. Forty five samples have been examined, where 37.8% were men and 62.2% were women. Most DHF cases were at the age of 8−14 years (47%). The mean platelets count after the day five of their hospitalization in both primary and secondary infections showed a significant increase (p<0.05), with the mean of 124.3×103/μL and 109.7×103/μL respectively. The same result was obtained with the MPV (p<0.05). In contrast of the finding, the mean of PDW showed no significant increase (p>0.05). It can be concluded that platelet count and MPV can be used as the early markers for the improvement of DHF patients during their hospitalization, so that the patients can be discharge and the period of their hospitalization will become shorten.